2014
DOI: 10.1371/journal.pone.0092625
|View full text |Cite
|
Sign up to set email alerts
|

Local Crop Planting Systems Enhance Insecticide-Mediated Displacement of Two Invasive Leafminer Fly

Abstract: Liriomyza sativae and L. trifolii are highly invasive leafminer pests of vegetable crops that have invaded southern China in recent years. Liriomyza sativae was the first of these species to invade China, but it is now being displaced by L. trifolii. The rate and extent of this displacement vary across southern China. In Hainan, monocultures of highly valuable cowpea are planted and treated extensively with insecticides in attempts to control leafminer damage. In Guangdong, cowpea fields are interspersed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Consequently, temperature‐mediated effects may contribute to the current ongoing displacement of L. sativae by L. trifolii in warm climatic areas of China . Furthermore, the competitive balance between these species can also be altered to the advantage of one species or the other by the general cropping system, with L. sativae being more susceptible to displacement in intensively managed cowpea crops, especially when grown as a monoculture . L. sativae appears to persist in more diverse host plant communities, where it has greater reproductive success than L. trifolii .…”
Section: Influence Of Abiotic Factors On Species Displacementmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, temperature‐mediated effects may contribute to the current ongoing displacement of L. sativae by L. trifolii in warm climatic areas of China . Furthermore, the competitive balance between these species can also be altered to the advantage of one species or the other by the general cropping system, with L. sativae being more susceptible to displacement in intensively managed cowpea crops, especially when grown as a monoculture . L. sativae appears to persist in more diverse host plant communities, where it has greater reproductive success than L. trifolii .…”
Section: Influence Of Abiotic Factors On Species Displacementmentioning
confidence: 99%
“…L. sativae appears to persist in more diverse host plant communities, where it has greater reproductive success than L. trifolii . Given the generally greater pest problems experienced with L. trifolii compared with L. sativae in southern China, maintaining untreated hosts that are better suited to L. sativae may increase the likelihood of its persistence in the presence of L. trifolii and aid in improved leafminer management …”
Section: Influence Of Abiotic Factors On Species Displacementmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has demonstrated that differential susceptibility to insecticides may increase the likelihood of one species being replaced by another, thus driving changes in population demographics171819. Two of the most commonly applied insecticides for management of thrips in China are avermectin and beta-cypermethrin15.…”
mentioning
confidence: 99%